2017
DOI: 10.3892/ijo.2017.4188
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol attenuates the sensitivity of glioblastoma to temozolomide through the suppression of Cx43‑mediated gap junction intercellular communication

Abstract: Analgesics and antineoplastic drugs are often used concurrently for cancer patients. Our previous study reported that gap junctions composed of connexin32 (Cx32) was implicated in the effect of analgesics on cisplatin cytotoxicity. However, the effect of analgesic on the most widely expressed connexin (Cx), connexin43 (Cx43), and whether such effect mediates the influence on chemotherapeutic efficiency remain unknown. By manipulation of Cx43 expression or gap junction function, we found that there were gap jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Furthermore, knockdown of Cx43 using a small interfering RNA (siRNA), together with TMZ, substantially induced cell death, suggesting that Cx43 renders U87MG and T98G cells resistant to TMZ. These results were consistent with another study, in which shRNA decrease of Cx43 expression and loss of GJIC sensitized U87MG cells to TMZ [15]. Lai and colleagues exposed Cx43-low/TMZ-sensitive U251 GBM cells to a low dose of TMZ to select a TMZ-resistant U251 clone and subsequently found that TMZ-resistant U251 cells expressed higher levels of Cx43 and, intriguingly, that the MGMT gene showed reactivated expression in the TMZ-resistant clone [45 • ].…”
Section: Connexin43 Expression and Tmz Resistancesupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, knockdown of Cx43 using a small interfering RNA (siRNA), together with TMZ, substantially induced cell death, suggesting that Cx43 renders U87MG and T98G cells resistant to TMZ. These results were consistent with another study, in which shRNA decrease of Cx43 expression and loss of GJIC sensitized U87MG cells to TMZ [15]. Lai and colleagues exposed Cx43-low/TMZ-sensitive U251 GBM cells to a low dose of TMZ to select a TMZ-resistant U251 clone and subsequently found that TMZ-resistant U251 cells expressed higher levels of Cx43 and, intriguingly, that the MGMT gene showed reactivated expression in the TMZ-resistant clone [45 • ].…”
Section: Connexin43 Expression and Tmz Resistancesupporting
confidence: 93%
“…An added layer of complexity is afforded through channel-independent mechanisms via the stabilization or destabilization of multiprotein complexes mediated through protein binding sites on the connexin protein. Connexin43 (Cx43) is the most ubiquitous connexin and in addition to having critical regulatory and developmental roles in many tissues, has been implicated as a driver of tumor invasion [11 •• ], a marker of tumor progression [12], and an inducer of TMZ resistance in GBM cells [6 •• ,1315,16 •• ]. Furthermore, the expression and function of connexins in the microenvironment of malignant glioma is an evolving field, where recent studies investigating the function of Cx43 in the tumor microenvironment reveal that Cx43 in peritumoral cells regulates gliomagenesis, tumor progression, and treatment resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As a conventional therapeutic strategy, surgical resection supplemented with chemotherapy and radiotherapy confers a poor prognosis in patients with gliomas (Stupp et al, 2005). This poor prognosis is mainly caused by the resistance to the chemotherapeutic alkylating agents such as temozolomide (TMZ), and the invasive nature of the tumor cells (Sin et al, 2012, 2016; Wang et al, 2018). In the TMZ-resistant GBM cells, Cx43 expression showed a significant upregulation.…”
Section: Cx43 In Gliomamentioning
confidence: 99%
“…The incidence of glioma is also relatively high, presenting in 5.26 per 100 000 individuals. [3][4][5] Tramadol, a non-opioid central analgesic, attenuates the sensitivity of glioblastoma to the chemotherapy drug temozolomide through the suppression of Cx43-mediated gap junction intercellular communication. The median overall survival rates for low-grade gliomas (WHO grade II), anaplastic gliomas (WHO grade III) and glioblastomas (GBM, WHO IV) are 78.1, 37.6 and 14.4 months, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 The current standard of treatment requires surgical resection followed by radiotherapy and chemotherapy, but the rate of survival remains poor. 3 In contrast, research has suggested that these types of drugs, such as propofol, lidocaine, sevoflurane and thiopental, may suppress the proliferation and invasion of glioma cells and, therefore, be beneficial in the control of cancer progression. 2 The refractory character of glioma is indeed the major cause of treatment failure, but many other factors also influence therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%